Exploring lesson study in postsecondary education through self-study. Issue 4 (4th August 2020) - Moghaddam, Alireza; Arnold, Christine; Azam, Saiqa; Goodnough, Karen; Maich, Kimberly; Penney, Sharon; Young, Gabrielle
Abstract : Purpose: The purpose of this collaborative self-study inquiry was to enhance the professional practice of faculty members through the adoption of lesson study. A seven-member faculty of education self-study group engaged in lesson study in a computer and learning resources for primary/elementary teachers' course with teacher candidates. Design/methodology/approach: This study focused on providing teacher candidates with increased opportunities for action and expression during in-class instruction. This collaborative lesson study inquiry (Fernandez et al., 2003; Fernandez and Yoshida, 2004; Murata, 2011) involved the four-step process of planning, doing, checking and acting (PDCA) (Cheng, 2019). Several data collection methods were adopted and data sources analyzed. Findings: Challenges the group encountered during the study included ascertaining the goals of lesson study and offering critical feedback to each other. While this made decision-making more intricate and intentional, there was exceptional value in participating in the lesson study process. The results revealed three overarching themes: 1) challenges in classroom observations; 2) hesitation in providing supportive feedback to colleagues and 3) deliberations regarding what constitutes expertise within subject-specific preservice teacher education. Originality/value: While lesson study has been adopted fairly extensively in K-12 settings, its adoption in postsecondary education is limited (Chenault, 2017). Considering the merits of lesson study for K-12 practitioners, this research investigated the similar advantages that lesson study might have for postsecondary education faculty, students and programs.